Respuesta :

Answer: y=-2x+6

Step-by-step explanation:

The equation for slope-intercept form is : y=mx+b

  • m=slope
  • b=y-intercept

----------------------------------------------------------------

First Step: find the slope

- (y2-y1)/(x2-x1)

GIven

x1=0

y1=6

x2=4

y2=-2

Solve

 (y2-y1)/(x2-x1)

=(-2-6)/(4-0)

=-8/4

=-2

Second Step: find the y-intercept

Given

y=-2x+b

Substitute one of the points into the equation

y=-2x+b

(-2)=-2(4)+b

-2=-8+b

b=6

Hope this helps!! :)

Please let me know if you have any questions